Modeling of conventional single slope solar still (CS4) with phase change material (PCM) - Santosa, Irfan; Dwi Septiyanto, Muhamad; Andriyanto, Sholikhin; Budiana, Eko Prasetya Budiana; Hadi, Syamsul; Wijayanta, Agung Tri (Universitas Trunojoyo Madura, 2025)
This study investigates the capability of two-dimensional Computational Fluid Dynamics (CFD) simulation to estimate the temperature distribution pattern and velocity contours in a single slope solar still that uses soybean wax as a phase change material (PCM). A triangular mesh model is employed in the simulation. The basin geometry uses a mesh with 20,402 nodes and 10,000 elements, while the PCM geometry uses a mesh consisting of 9,272 nodes and 4,500 elements. This study introduces an equation developed based on the Dunkle, Bulk Motion, and Chilton-Colburn analogies to estimate the Nusselt number in the solar still. The water temperature (Tw), the inner surface temperature of the glass cover (Tg), and the PCM temperature (Tpcm) are determined experimentally, whereas the performance of the conventional solar distillation system is predicted theoretically using the experimental results. The results demonstrate that the use of soybean wax as a PCM positively influences the temperature distribution and streamline patterns within the single slope solar still. In the morning, the temperature and velocity distributions reveal that the isotherm lines are parallel to the lower right segment of the cavity, indicating that conduction is the dominant heat transfer mechanism. As the day progresses, the streamline pattern inside the cavity expands and becomes more curved, suggesting an increased influence of the convection process. These findings are consistent with the CFD analysis results, which show high accuracy in predicting Nusselt numbers. Furthermore, the comparison between daily distilled water productivity from experimental measurements and theoretical predictions shows good agreement.